Studi Putusan Hakim Pada Perkara Cerai Gugat Nomor 474/Pdt.G/2020/PA.JS Terhadap Hak Nafkah Iddah - Fatimatuz Zahro; Salsabila Annisa Rohmah (MASADIR: Jurnal Hukum Islam, 2022)
The Panel of Judges in deciding the case that the wife has the right of iddah (a period that must be lived by a woman after the death of her husband or after divorce, during which she cannot marry another man) for her claims against her husband. Therefore, to find out the reason for the non-provenance of nusyuz (a wife unreasonably refusing to comply with the wishes or orders of a legitimate husband) in obtaining the right to live iddah in the divorce law Number 474/Pdt.G/2020/PA.JS based on fiqh and UU Marriage Article 41 of 1974. This issue will be studied using a normative legal approach and a judge's decision study approach. The results of the analysis show that Decision Number 474/Pdt.G/2020/PA.JS concerning the issue of the right to live iddah in a divorce where the Panel of Judges carries out and decides various considerations in deciding the case: the ex-wife or plaintiff gets the right to live iddah from her ex-husband on the basis of considerations The law refers to Article 149 letter (b) of the KHI which basically states that if a marriage breaks up, the husband is obliged to provide a living. including food to eat and clothing to cover his wife's expenses during the period of iddah. Article 41 letter c of the Marriage Law states that the court can require the husband to provide maintenance or establish obligations for the wife.